2015
DOI: 10.1530/eje-15-0616
|View full text |Cite
|
Sign up to set email alerts
|

A role for 11C-methionine PET imaging in ACTH-dependent Cushing's syndrome

Abstract: Objective: We report our experience of functional imaging with 11 C-methionine positron emission tomography-computed tomography (PET-CT) co-registered with 3D gradient echo (spoiled gradient recalled (SPGR)) magnetic resonance imaging (MRI) in the investigation of ACTH-dependent Cushing's syndrome. Design: Twenty patients with i) de novo Cushing's disease (CD, nZ10), ii) residual or recurrent hypercortisolism following first pituitary surgery (Gradiotherapy; nZ8) or iii) ectopic Cushing's syndrome (nZ2) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 35 publications
2
63
0
1
Order By: Relevance
“…Alzahrani et al [24] obtained a sensitivity of 18 F-FDG-PET/CT of 58 % in locating ACTHsecreting adenomas and Feng et al [25] also found an unsatisfactory sensitivity of 53 %. The results with 11 C-Methionine-PET/CT seem to be promising, with a sensitivity of 100 % found by Feng et al [25] and Ikeda et al [26] (studies with 15 and 11 patients, respectively); nevertheless, these are still small series of patients and other authors like Koulouri et al found less positive results [27].…”
Section: Discussionmentioning
confidence: 90%
“…Alzahrani et al [24] obtained a sensitivity of 18 F-FDG-PET/CT of 58 % in locating ACTHsecreting adenomas and Feng et al [25] also found an unsatisfactory sensitivity of 53 %. The results with 11 C-Methionine-PET/CT seem to be promising, with a sensitivity of 100 % found by Feng et al [25] and Ikeda et al [26] (studies with 15 and 11 patients, respectively); nevertheless, these are still small series of patients and other authors like Koulouri et al found less positive results [27].…”
Section: Discussionmentioning
confidence: 90%
“…The identified pathologies included Cushing's disease (48%), thyrotropinsecreting pituitary adenoma (20%), acromegaly (12%), nonfunctioning pituitary adenoma (12%), prolactinoma (4%). Tumor volumes ranged from 195 mm 3 to 6702 mm 3 , with an average of 1452 mm 3 and median of 375 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A separate reconstruction was performed with each of the three attenuation maps (PETatl , PETZTE and PETCT). The reconstruction parameters were selected to mimic those of the PET/CT clinical protocol, while accounting for the limitations imposed by the different detector geometry: Fully 3D ordered subsets expectation maximization algorithm with time-offlight information (VPFX), iterations 9, subsets 8, matrix 128 × 128 × 89, voxel size 2.34 × 2.34 × 2.78 mm 3 , transaxial post-reconstruction Gaussian filter 4mm, axial filter 1:2:1, point-spread function, normalization, randoms, scatter, dead-time and decay corrections.…”
Section: Retrospective Pet Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a group of Cambridge team testified that 11C-methionine positron emission tomography–computed tomography may play a role in detection and treatment of ACTH-secreting tumors in Cushing syndrome. [13] Apart from surgical reintervention of the ACTH-secreting adenomas, there are alternatives including radiotherapy, adrenal surgery, and pharmaceutical therapy. [14] Progression has been made in the field of drug development, and pasireotide, [15] mifepristone, ketoconazole, metyrapone, and cabergoline [16] have approved effective in managing Cushing disease.…”
Section: Discussionmentioning
confidence: 99%